Institucionalização do ambiente virtual de aprendizagem no ensino superior: o caso da Universidade Federal do Paraná - Vieira, Ana Paula (2019)
This research describes through case study the institutionalization of the Virtual Learning Environment (VLE) at the Federal University of Paraná (UFPR), in all its phases, adoption, implementation, acceptance and dissemination of VLE through the free software Moodle used in the Applied Social Sciences Sector. The analysis of the institutionalization phases is based on the works of Tolbert and Zucker (2014) and Greenwood, Suddaby and Hinings (2002). Primary data were collected by means of semi-structured interviews with technical-administrative servers and teachers of the Administration and Information Management Courses and the Coordination of Integration of Distance Education Policies of UFPR. The documentary survey was used as a secondary source to complement the analysis of the institutionalization of the VLE. In this research, the techniques used were document analysis and thematic content from 2010 to 2018 with data triangulation. Technological changes have been shown to affect institutional relationships from the precipitating event stage of Greenwood, Suddaby and Hinings (2002) through new structural arrangements in the adoption of VLE. However, almost a decade after the regulation of distance workload in face-to-face undergraduate courses, institutional change is still in the habitalization phase of Tolbert and Zucker (2014) and points to the action of interest of social actors as the cause. obstructing the institutionalization flow of a new practice. The interest identified goes back to the historical origin of patriarchalism in Brazil, overlapping the social function of education and having the organizational field as the institutional sphere of disputed interests. In addition to corroborating the studies mentioned, this research brings its theoretical contribution by jointly analyzing the organizational flow of Tolbert and Zucker's institutionalization process (2014) and the strategic theorizing for the institutionalization of a new practice by Greenwood, Suddaby and Hinings (2002).